If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x -2x+1=x+6
We simplify the equation to the form, which is simple to understand
3x-2x+1=x+6
We move all terms containing x to the left and all other terms to the right.
+3x-2x-1x=+6-1
We simplify left and right side of the equation.
0x=+5
0=5
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 3x+11+7x+3=180 | | 12=3(x-9) | | 3x+5x+10=10x-2x+10 | | 12z^3=14z^2+48z | | 2x+18=4x+10 | | 7-4y=7 | | -9x-5y=27 | | 2*(ln(x))+1=0 | | x-4(x+3)=12 | | 8q+5=2 | | 50q-43=52q-18 | | 250=14w+9g | | 6x-1=7(x+9) | | 2(x-8)=2x+6 | | 2x^2+10X+3=3 | | 4.5g+0.75=18.75 | | 4.5+0.75=18.75 | | 3x=5(x+3)-s | | f(x)=3x^2-9x+6 | | -4=2-3p | | 4k-5=-17 | | -15r+5=50 | | x+4x+(4x-49)=437 | | 5(x-4)+3=7x | | 3x^2-2x-30=0 | | 18=5p-2 | | 60xn=120 | | 8xn=32000 | | 7(x-4)+8x=12+14 | | 1xn=10 | | 9+9+2(x-2)=5x+8-2x | | 12x+3=26 |